The effects of TiO2 Nanoparticles on Flexural Strength of Self-Polymerized Resins: In Vitro Study - Firas Abd Kati (Journal of Techniques)
Self-polymerized resins are extensively utilized in removable prosthodontics for a variety of applications in maxillofacial rehabilitation, including interim appliances, repairs, relines, customized trays, and record bases. These materials, on the other hand, are prone to fracture. The goal of this study was to see how titanium dioxide nanoparticles affected the flexural strength of self-polymerized resins. A total of 30 samples were prepared from self-polymerized acrylic resins (control, 1% TiO2, and 2% TiO2). Using a universal testing machine, all samples were subjected to a flexural strength test until they fractured. The data were analyzed with SPSS version 20, and the Duncan test and ANOVA tests were used to compare all groups. The results showed that TiO2 increased the flexural strength of acrylic resins substantially when compared to the control. Furthermore, significant differences (P<0.001) were found among all groups. The addition of TiO2 increases the flexural strength of acrylic resins.